2014
DOI: 10.1371/journal.pgen.1004548
|View full text |Cite
|
Sign up to set email alerts
|

An Otx/Nodal Regulatory Signature for Posterior Neural Development in Ascidians

Abstract: In chordates, neural induction is the first step of a complex developmental process through which ectodermal cells acquire a neural identity. In ascidians, FGF-mediated neural induction occurs at the 32-cell stage in two blastomere pairs, precursors respectively of anterior and posterior neural tissue. We combined molecular embryology and cis-regulatory analysis to unveil in the ascidian Ciona intestinalis the remarkably simple proximal genetic network that controls posterior neural fate acquisition downstream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 72 publications
(144 reference statements)
2
63
1
Order By: Relevance
“…Msxb expression in a-lineage column 3 is also downstream of Nodal (Fig. S1), as has been shown previously for b-lineage Msxb expression (Roure et al, 2014). Using Msxb-MOs, we found that while knockdown of Msxb alone had no effect on Gsx expression, combined inhibition of both Msxb and Snail resulted in strong ectopic expression of Gsx in column 3 at the neurula stage ( Fig.…”
Section: Snail and Msxb Repress Gsx In Columnsupporting
confidence: 85%
“…Msxb expression in a-lineage column 3 is also downstream of Nodal (Fig. S1), as has been shown previously for b-lineage Msxb expression (Roure et al, 2014). Using Msxb-MOs, we found that while knockdown of Msxb alone had no effect on Gsx expression, combined inhibition of both Msxb and Snail resulted in strong ectopic expression of Gsx in column 3 at the neurula stage ( Fig.…”
Section: Snail and Msxb Repress Gsx In Columnsupporting
confidence: 85%
“…At the 16-cell stage, Fgf9/16/20 is activated in the vegetal hemisphere and induces neural fate in the animal hemisphere (Bertrand et al, 2003;Hudson et al, 2003;Hudson and Lemaire, 2001;Khoueiry et al, 2010;Ohta and Satou, 2013;Ohta et al, 2015;Roure et al, 2014). Tfap2-r.b is first expressed in the entire animal hemisphere, and then the expression disappears in the neural lineage at the 64-cell stage (Fig.…”
Section: Downregulation Of Tfap2-rb In Non-epidermal Cellsmentioning
confidence: 98%
“…S1), and give rise to the dorsal row of the nerve cord, epidermal sensory neurons and epidermal cells along the nerve cord (Imai et al, 2006;Pasini et al, 2006;Roure et al, 2014;Waki et al, 2015). Whereas Msx was expressed normally in embryos injected with the lacZ or Tfap2-r.b MOs, it was greatly reduced in Sox1/2/3 morphants ( Fig.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…TFs are known to play promiscuous roles in developmental systems, and can thus be co-opted to new functional roles (reviewed in Cheatle Jarvela and Hinman 2015). For instance, studies provide evidence that deeply conserved TFs across animal lineages have been co-opted to perform novel functional roles in specific lineages, such as Tbrain in echinoderms (Hinman et al 2007), Otx in ascidians (Roure et al 2014), and Hox genes in Haliotis asinina (Hinman et al 2003). Given these examples, it is possible that coexpressed TFs between sponges and sea urchins are not indicative of conserved regulatory roles involved in metamorphosis.…”
Section: Homology Vs Convergence: When Did Biphasy Evolve?mentioning
confidence: 99%